The value discovery of foreign direct investment: Based on the study of the crowding-out effect of zombie enterprises on investment - Song Chen; Meixu Ren; Chuanzhen Li (Journal of Innovation & Knowledge (JIK), 2024)
Foreign direct investment (FDI) is of great significance to the economic development of developing countries; it infuses capital into enterprises, while propeling both technological advancement and economic efficiency. We examine whether zombie enterprises crowd out FDI inflows and whether the institutional environment can alleviate this effect. Using the Chinese Industrial Enterprise Database from 2003 to 2013 to calculate zombie shares at the prefecture-level cities and applying the OLS and instrumental variable estimation, we find that the larger the zombie shares, the less FDI inflows. That is, zombies do crowd out FDI inflows - a finding robust to specifications. We also find that the geographical advantage and greater openness to the outside world can alleviate the crowding-out effect. Further, we investigate the moderating effect of the institutional environment on the crowding-out effect. We find that market segmentation and government corruption will aggravate the crowding-out effect while strengthening intellectual property protection, improving the trust environment, and factor market development will alleviate it. Overall, our study explains impediments to FDI inflows by accounting for zombie enterprises. It provides insights for local governments seeking to clean up zombies and strengthen the institutional environment to attract FDI inflows.
Keywords: F21; O17; R38; 650; Zombie enterprise; Crowding-out effect; FDI; Update of technology